Human Adrenocortical Carcinoma (NCI-H295R) Cell Line as an In Vitro Cell Culture Model for Assessing the Impact of Iron on Steroidogenesis - Knazicka, Z; Fialkova, V; Duranova, H; Bilcikova, J; Kovacikova, E; Miskeje, M; Valkova, V; Forgacs, Z; Roychoudhury, S; Massanyi, P; Lukac, N (Folia biologica, 2021)
The aim of this in vitro study was to examine the dose-dependent effects of iron as a potential endocrine disruptor in relation to the release of sexual steroid hormones by a human adrenocortical carcinoma (NCI-H295R) cell line. The cells were exposed to different concentrations (3.90, 62.50, 250, 500, 1000 μM) of FeSO4.7H2O and compared with the control group (culture medium without FeSO4.7H2O). Cell viability was measured by the metabolic activity assay. Quantification of sexual steroid production was performed by enzyme-linked immunosorbent assay. Following 48 h culture of the cells in the presence of FeSO4.7H2O, significantly (P < 0.001) increased production of progesterone was observed at the lowest concentration (3.90 μM) of FeSO4.7H2O, whereas the lowest release of progesterone by NCIH295R cells was noted after addition of 1000 μM of FeSO4.7H2O, which did not elicit cytotoxic action (P > 0.05). Testosterone production was substantially increased at the concentrations ≤ 62.50 μM of FeSO4.7H2O. Lower levels of testosterone were recorded in the groups with higher concentrations (≥ 250 μM) of FeSO4.7H2O (P > 0.05). The presented data suggest that iron has no endocrine disruptive effect on the release of sexual steroid hormones, but its toxicity may be reflected at other points of the steroidogenesis pathway.
Keywords: Iron; lidé; železo; adrenokortikální nádory; Cell Culture Techniques; adrenokortikální karcinom; Humans; Adrenal Cortex Neoplasms; Cell Line, Tumor; Adrenocortical Carcinoma; nádorové buněčné linie; buněčné kultury